In vitro dry matter disappearance using roe deer inocula from summer and winter - Holand, Øystein (Rangifer, 1993)
In vitro dry matter disappearance (IVDMD) of 12 forages were determined using ruminai inocula from 10 European roe deer (Capreolus capreolus L.) collected in summer and winter. There was significant difference in the ability of winter and summer inocula to digest winter and summer forages respectively. Each of the 6 summer forages had a significantly higher IVDMD in ruminal inocula of animals collected in summer versus winter. However, no significant difference in IVDMD of winter versus summer inocula was observed for each of the 6 winter forages. These results suggest adaption, although limited, by ruminal microorganisms in roe deer to winter forages or a potential problem in standard in vitro laboratory procedures when using animals on a high-fiber diet as inocula donors.